Stress in preschool children and its correlation with salivary chromogranin A - Sunil Kumar Jena; Biswabhusan Mohanty (Wolters Kluwer Medknow Publications, 2016)
Background: When preprimary school students enter school, there is definitely a chance of developing psychological stress, which for a prolonged period is harmful to their lives. Different researchers have proved that salivary chromogranin A is a potent biomarker of psychological stress. There are very less studies regarding preschool stress. Thus, we proposed this study to find out the severity of stress in preschool children and its correlation with salivary chromogranin A. Materials and Methods: Fifty-six preprimary school students in the age group of 2.5-5 years were involved in this study. The severity of stress was evaluated by a self-structured questionnaire, preprimary stress questionnaire (PPSQ) and these questionnaires were distributed to different study groups, i.e., no stress, mild stress, moderate stress, and severe stress. Salivary chromogranin A was estimated by enzyme-linked immunosorbent assay (ELISA) test. Result: Out of 56 participants, 7 did not face stress, 14 faced mild stress, 14 faced moderate stress, and 21 faced severe stress. The mean rank stress score rose with severity of stress and was found to be significant. The mean salivary chromogranin A level was analyzed between the different groups and found to be significant at P < 0.001. Correlation coefficient between stress and salivary chromogranin A was 0.875 and significant at P < 0.01. Conclusion: We found that preprimary school students faced stress in different severities and their salivary chromogranin A was raised. Salivary chromogranin A was considered as a biomarker of psychological stress in this study because it is noninvasive and easy to collect from the samples of all the small children with convenience.